IMPROVING STUDENTS’ VOCABULARY THROUGH SONGS - Ilinawati Ilinawati; Yokie Prasetya Dharma (STKIP Persada Khatulistiwa Sintang, 2018)
The study was about improving students’ vocabulary through English song. The subject of the study were first semester students of English language study program, STKIP Persada Khatulistiwa Sintang,Academic Year 2018/2019 which consisted of 22 students. This study aimed to increase students’ vocabulary through songs.The method of this research was qualitative research and the object was teaching vocabulary through English song.This was classroom action research which consisted of one cycle.In collecting the data, the researchers used observation sheet, Fieldnotes and test. The result of this research showed that the use of song succeeded improving students’ vocabulary. The result of the test shown that mean score was 80,25, it was good cathegory.The improvement of the teaching learning process was based on the improvement of teaching learning behaviour in the classroom. The change of behaviour was notified from the classroom observation, fieldnotes which were discussed with the collaborator in the reflection stage. Song was found out helpful to improve students’ vocabulary mastery for first semester students of English language study program, STKIP Persada Khatulistiwa Sintang, Academic year 2018/2019.Keywords: Vocabulary Mastery, English Songs